PELATIHAN PSIKOEDUKASI UNTUK MENINGKATKAN HARGA DIRI PADA REMAJA - Abdy Ihdalumam; Ibnu Fajar, Al Amin; Puspitasari, Devi (Ikatan Dosen Menulis, 2023)
A critical period in an individual's development, adolescence is distinguished by cognitive, physical, and environmental transformations. This study examines the significance of adolescent self-esteem, particularly in rural regions where mental health services and educational opportunities are scarce. In order to foster students' self-esteem awareness, community service was organised in MA Anjasmoro, Jarak Village, Jombang Regency. Eleven MA Anjasmoro students participated in the implementation of psychoeducational training; the results indicated a significant increase in self-esteem following the training. The statistical significance of the difference between the pretest and posttest was confirmed by the Wilcoxon test. In addition to enhancing students' knowledge, the training facilitated the growth of their social and emotional competencies. The findings of the research indicated that the implementation of psychoeducation at MA Anjasmoro effectively enhanced the self-esteem of adolescent students. Students gained new insights regarding character, positive mentality, and positive behaviours as a result of these findings. Psychoeducation has surfaced as a viable substitute for enhancing the self-esteem of adolescents, particularly within the educational landscape of rural regions.